„Green” Public Relations (Public relations in the sector of products and services for Polish agriculture) - Włodarski, Sebastian (Applied Studies in Agribusiness and Commerce, 2007)
The field of Public Relations has undoubtedly been assuming growing importance in Poland. Understood as an element of marketing communication or a function of company management, it has a significant impact on company’s external and internal environment. According to Puls Biznesu3 the value of the Polish PR market amounted to 250m PLN in 2005, which is a 20% increase as compared to 2004. According to the author Urszula S ´wiatl⁄owska, “the turnover of PR agencies is growing and even smaller companies demonstrate their interest in the services”. Considering this, it can be assumed that PR activities will soon be initiated by many smaller Polish companies, often connected with the agricultural sector. The change discussed by the authors of the article reflects the phenomenon of PR’s growing importance among other communication channels in Poland.